INNOCENTI, Perla. Cultural Networks in Migrating Heritage: Intersecting Theories and Practices across Europe. Farnham: Ashgate. 2015. 180 pages. ISBN 978-1-4724-4813-2. £60.00. (2016) - Davies, Kat
No abstract available